Exploring self toward expanding teaching, teacher education and practitioner research - Ergas, Oren; Ritter, Jason K. (Advances in research on teaching, 2020)
Against the backdrop of a pull toward external standards and accountability, this collection of chapters re-grounds us in the importance of bringing the 'self' to the foreground of the discourse of teaching, teacher education and practitioner research. Showcasing the work of an international group of scholars whose research and teaching in higher education institutions focuses on working with teachers at the intersection of their professional and personal identities, this book explores diverse practices, such as self-study and mindfulness, that examine, evoke and invoke the self. The authors articulate a range of important questions: What do we mean when we speak of 'self' in the domain of teaching, and its research and practice? Why is it important for teachers to explore themselves in an age of high-stakes testing and performativity? Developing explorations of 'self' hat stem from a variety of epistemologies spanning Western and East-Asian philosophical schools of thought, this book delves into a rich journey toward the deep, ancient and ever-present question of who we are, opening up various theoretical and practical methods for advancing the endeavors of teaching and teaching research.